Geotextile Selection Methods for the Lithuanian Road and Street Structures - Audrius Vaitkus (The Baltic Journal of Road and Bridge Engineering)
This summary of the author’s PhD thesis supervised by Prof Dr Alfredas Laurinavičius and defended on 7 December 2007 at the Vilnius Gediminas Technical University. The thesis is written in Lithuanian and is available from the author upon request. In chapter 1 describes the existing problem, the need for the use of geotextiles for the separation of road and street structures. Also, the relevance of the research, the scientific novelty and originality of the dissertation, its aim and practical importance. Chapter 2 presents analysis of the geotextile selection methods for the separation of structural layers. In chapter 3 presented experimental research of the use of geotextiles for the separation of roads and streets pavement structure layers. Finally in chapter 4 the geotextile selection method for the use in the Lithuanian roads and streets pavement structures is presented. Developed geotextile selection method reflects the need for the use of geotextile, takes into consideration the factors having the impact on the occurrence of geotextile damages during pavement installation and in the course of road operation.